Correction: Sign language mobile apps: a systematic review of current app evaluation progress and solution framework (Evolving Systems, (2024), 15, 2, (669-686), 10.1007/s12530-023-09494-0) - Dianes A/P David Emmanuel, Salem Abdullah Salem Garfan (Tanjung Malim, 2024)
Correction: Sign language mobile apps: a systematic review of current app evaluation progress and solution framework (Evolving Systems, (2024), 15, 2, (669-686), 10.1007/s12530-023-09494-0) by Dianes A/P David Emmanuel, Salem Abdullah Salem Garfan